2017
DOI: 10.3390/molecules22091564
|View full text |Cite
|
Sign up to set email alerts
|

Brush Polymer of Donor-Accepter Dyads via Adduct Formation between Lewis Base Polymer Donor and All Carbon Lewis Acid Acceptor

Abstract: A synthetic method that taps into the facile Lewis base (LB)→Lewis acid (LA) adduct forming reaction between the semiconducting polymeric LB and all carbon LA C60 for the construction of covalently linked donor-acceptor dyads and brush polymer of dyads is reported. The polymeric LB is built on poly(3-hexylthiophene) (P3HT) macromers containing either an alkyl or vinyl imidazolium end group that can be readily converted into the N-heterocyclic carbene (NHC) LB site, while the brush polymer architecture is conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…In some cases, the employment of all organic LPs, such as B­(C 6 F 5 ) 3 /PR 3 (NHC or amine) ,,, and Me 3 SiNTf 2 /PR 3 for the polymerizations of acrylates, B­(C 6 F 5 ) 3 /DABCO for the epimerization of meso -LA to rac -LA, Fmes 2 BF/aniline for the ROP of NCA, and BEt 3 /LB for the copolymerization of CO 2 (COS) with epoxides, ,, has been characterized as a “green” and/or “sustainable” synthesis of metal-free polymeric materials. (5) Advancing materials chemistry by applying the principles of the LPP and LP chemistry as a new platform, as demonstrated by highlighted examples such as the development of a new type of reversible/dynamic cross-linking system that can be reshaped, reprocessed, or repaired, and has also been exploited in stimulus-responsive and self-healing materials, , the construction of a novel gelator with a more specific and triggerable response, and the utilization of LPP for novel polymer compositions and architectures relevant to organic photovoltaic applications. ,, …”
Section: Summary and Outlookmentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, the employment of all organic LPs, such as B­(C 6 F 5 ) 3 /PR 3 (NHC or amine) ,,, and Me 3 SiNTf 2 /PR 3 for the polymerizations of acrylates, B­(C 6 F 5 ) 3 /DABCO for the epimerization of meso -LA to rac -LA, Fmes 2 BF/aniline for the ROP of NCA, and BEt 3 /LB for the copolymerization of CO 2 (COS) with epoxides, ,, has been characterized as a “green” and/or “sustainable” synthesis of metal-free polymeric materials. (5) Advancing materials chemistry by applying the principles of the LPP and LP chemistry as a new platform, as demonstrated by highlighted examples such as the development of a new type of reversible/dynamic cross-linking system that can be reshaped, reprocessed, or repaired, and has also been exploited in stimulus-responsive and self-healing materials, , the construction of a novel gelator with a more specific and triggerable response, and the utilization of LPP for novel polymer compositions and architectures relevant to organic photovoltaic applications. ,, …”
Section: Summary and Outlookmentioning
confidence: 99%
“…The same group recently designed and synthesized the linked D−A dyad P3HT-(CH 2 ) 3 -MIM-C 60 [Scheme 58B; P3HT = poly(3-hexylthiophene)] and brush polymer of dyads P[P3HT-(CH 2 ) 3 -VIM-C 60 ] (Scheme 58C), via a facile "click"-type LB−LA adduct forming approach (Scheme 59). 465 The authors found that a change of the topology of the P3HT-C 60 dyad from a linear to brush architecture enhanced the crystallinity and T m of the P3HT domain, and interestingly, covalently linked D−A dyads showed an extended lightharvesting wavelength range of the active layer and increased generation efficiency of the excitons of the semiconducting polymer, when compared with control systems where C 60 is either absent or unlinked. These interesting findings should provide a promising approach to control the morphology of the D/A active layer in organic photovoltaic applications.…”
Section: Lewis Pairs and Polymerization In Materials Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Chen’s team demonstrated that poly(3-hexylthiophene) macromer anchored with alkyl or vinyl imidazolium end groups can be readily converted into a polymeric NHC Lewis base that is capable of binding to Lewis acidic C 60 to form a single donor-acceptor dyad or brush of donor-acceptor dyads. The special architecture of brush donor-acceptor dyads provides promising potential applications in polymer-based solar cells [ 13 ]. In a different way, Jäkle and co-workers reported the interaction pattern between a polymeric Lewis acid and a telechelic Lewis base [ 14 ].…”
mentioning
confidence: 99%